Socio-Economic Perspectives Of Language Learning Motivation: The Case Of Yemeni EFL Undergraduates At The Hadramout University Of Science & Technology - Al-Timimi, Rais Ahmed (2011)

(untitled)
The concept of integrativeness in Foreign Language Learning (FLL) contexts has been theoretically reformulated recently by scholars in the field of motivational research such as Csizér and Dörnyei (2005). The reformulated concept takes into consideration the notion of “possible selves” which refers to the desire of language learners to learn or use the Target Language (TL) to create an identity or self image that is congruous with some socio-economic/cultural traits in their closer environment.